First description of the female of the jumping spider Balmaceda nigrosecta Mello-Leitão (Salticidae, Dendryphantini, Marpissina) - Rubio, Gonzalo Daniel (2016)
The female of Balmaceda nigrosecta Mello-Leitão, 1945 is described and illustrated for the first time. In addition, this paper further illustrates the male, and provides the first known observations on the natural history of this species, including habitat, cohabitation, and prey capturedata.